PENGARUH MODEL PERMAINAN FINDING MY SECRET WORD TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Farhanah, Laila; Arifin, Fatkhul (PD PGMI se Indonesia, 2021)
The purpose of this study was to determine the effect of using the game finding my secret word on stdents mathematical communication ability. This research was conducted at SD Negeri Jampang 03 class V in the academic year 2019/2020. The research method used was quasi experiment with The Nonequivalent Posttest-Only Group Design. Sample this study amounted to 58 students consisting of 29 experimental class students and 29 control class students. The instrument used in this study was a matter of essay. The data obtained were analyzed by Independent Sample t-Test which produced Sig. (2-tailed) of 0.005 < 0.05, then H0 is rejected and H1 is accepted. This shows that the average value of students mathematical communication ability taught using the game finding my secret word is higher than the average value of students mathematical communication ability taught by conventional learning. Thus, the use of the game finding my secret word has a significant affects on student mathematical communication ability.Â